Identifying genetic variants associated with sugar intake and appraising the genetic correlations with cardiovascular outcomes - Janzi, Suzanne; Ramne, Stina ; 0000-0003-1291-4494; Kou, Minghao; Lu, Xinmei; Stubbendorff, Anna ; 0000-0001-9851-6213; Ke, Chaofu; Borné, Yan; Qi, Lu; Sonestedt, Emily ; 0000-0002-0747-4562 (Clinical Nutrition, 2025)
BACKGROUND: The evidence linking sugar intake to cardiovascular disease risk remains largely inconclusive, with variations observed across different subgroups of sugar intake. In addition, studies on genetic markers of sugar intake are scarce, especially for different sugar subgroups. OBJECTIVE: This genome-wide association study (GWAS) aimed to investigate genetic variants associated with the intake of free sugars and sweet-tasting sugars (i.e., sucrose and monosaccharides) and to explore the relationship between sugar intake and cardiovascular disease risk using genetic markers. METHODS: We identified single-nucleotide polymorphisms (SNPs) associated with sugar intakes in two large cohorts: the Malmö Diet and Cancer Study (n = 25,660) and the UK Biobank (n = 141,437). We further examined whether the associations were independent of Body Mass Index (BMI), smoking status, and educational level. Finally, we investigated the genetic correlations between sugar intake and cardiovascular outcomes using data from different populations. RESULTS: For free sugar intake, GWAS-significant associations were found with SNPs in the FTO gene, in an intergenic region on chromosome 18, and near the FGF21 gene. For sweet-tasting sugar intake, the lead SNP was located near the FGF21 gene. The associations between sugar intake and the FTO SNPs were dependent on BMI, whereas this dependency was not observed for the FGF21-adjacent SNPs. Genetic correlations were found between both free sugar intake and sweet-tasting sugar intake and lower HDL cholesterol levels and heart failure risk, as well as higher log-triglyceride levels and risks of ischemic stroke and atrial fibrillation. CONCLUSION: The findings of this study indicate associations mainly between SNPs near the FGF21 gene and the FTO gene and both free and sweet-tasting sugar intake. Genetic correlations were found between both free sugar intake and sweet-tasting sugar intake and lower HDL cholesterol levels and heart failure risk, as well as higher triglyceride levels and risks of ischemic stroke and atrial fibrillation.
Copyright © 2025. Published by Elsevier Ltd.